GENRE AND ITS APPLICATION IN LANGUAGE LEARNING - Amrin Saragih (Universitas Negeri Padang, 2013)
Language is a social phenomenon. The implication is that the use of language is determined by the social context. One of the elements of social context is culture. Thus, the use of language is culturally bound where such a use of language is technically termed as genre. Specifically, genre is defined as staged goal-oriented social activities. With reference to the definition, a genre-based language learning is developed. This paper addresses descriptions of genre and a language learning technique with reference to genre theory.